Manuscript and print in late medieval and early modern Britain : essays in honour of Professor Julia Boffey - Atkin, Tamara, 1981-; Rajsic, Jaclyn, 1984- (D.S. Brewer, 2019)
The production, transmission, and reception of texts from England and beyond during the late medieval and early renaissance periods are the focus of this volume. Chapters consider the archives and the material contexts in which texts were produced, read, and re-read; the history of specific manuscripts and early printed books; and some of the continuities and changes in literary and book production, dissemination, and reception in the fifteenth and sixteenth centuries. Responding to Professor Julia Boffey's pioneering work on medieval and early Tudor material and literary culture, they cover a range of genres - from practical texts written in Latin to works of Middle English poetry and prose, both secular and religious - and examine an assortment of different reading contexts: lay, devotional, local, regional, and national. -- Back cover.